Pengembangan Auto CAD dengan vB untuk Desain Pola Coran dan Cetakan Produk Pulley Standar Tipe Taper Lock - Muhammad Kusumawan Herliansyah (Faculty of Engineering, Universitas Gadjah Mada, 2004)
dan Adi NugrohoJl. Grafika No. 2, Kampus UGM, Yogtakarta 55281AbstractThis paper presents the development of automatic casting design system for Taperlockpulley type. This system is intended to assist casting designer in pattern design, to reduce designtime, and to minimize error in transfering product design data into pattern design.The input of this system is data base of taper lock pulley's catalogue in mdb format, whilethe output is design of the pattern drawing in 2D and 3D solid. Moreover to generate patterndesign is around 59 second.Keywords: casting, pattern, automat ic.l.